Rabies Virus at the Beginning of 21st Century - Tkachev, Sergey (Veterinary Medicine and Science, 2022)
Despite significant worldwide progress in fighting rabies, a zoonotic viral disease, it remains an important public health concern, causing approximately 50,000 human cases per year. This book summarizes current knowledge regarding rabies, the prevalence and genetic diversity of the rabies virus, and modern approaches to rabies diagnosis, prevention, and treatment. It is a useful resource for scientists, doctors, and students.